The Nutrient-Responsive Molecular Chaperone Hsp90 Supports Growth and Development in Drosophila - Ohhara, Yuya; Hoshino, Genki; Imahori, Kyosuke; Matsuyuki, Tomoya; Yamakawa-Kobayashi, Kimiko (Frontiers in Physiology, 2021)
Animals can sense internal nutrients, such as amino acids/proteins, and are able to modify their developmental programs in accordance with their nutrient status. In the fruit fly, Drosophila melanogaster, amino acid/protein is sensed by the fat body, an insect adipose tissue, through a nutrient sensor, target of rapamycin (TOR) complex 1 (TORC1). TORC1 promotes the secretion of various peptide hormones from the fat body in an amino acid/protein-dependent manner. Fat-body-derived peptide hormones stimulate the release of insulin-like peptides, which are essential growth-promoting anabolic hormones, from neuroendocrine cells called insulin-producing cells (IPCs). Although the importance of TORC1 and the fat body-IPC axis has been elucidated, the mechanism by which TORC1 regulates the expression of insulinotropic signal peptides remains unclear. Here, we show that an evolutionarily conserved molecular chaperone, heat shock protein 90 (Hsp90), promotes the expression of insulinotropic signal peptides. Fat-body-selective Hsp90 knockdown caused the transcriptional downregulation of insulinotropic signal peptides. IPC activity and systemic growth were also impaired in fat-body-selective Hsp90 knockdown animals. Furthermore, Hsp90 expression depended on protein/amino acid availability and TORC1 signaling. These results strongly suggest that Hsp90 serves as a nutrient-responsive gene that upregulates the fat body-IPC axis and systemic growth. We propose that Hsp90 is induced in a nutrient-dependent manner to support anabolic metabolism during the juvenile growth period.